2004
DOI: 10.1590/s1413-70542004000400025
|View full text |Cite
|
Sign up to set email alerts
|

Alteração da carga de carrapatos de bovinos sob a ingestão de diferentes níveis do resíduo do beneficiamento do alho

Abstract: RESUMOTrinta bovinos machos, mestiços, castrados, provenientes de rebanhos leiteiros do sul de Minas, foram utilizados para avaliar o efeito da ministração de resíduo do beneficiamento do alho (RBA) na alimentação de bovinos sobre o desempenho e a alteração da carga de carrapatos. Foram utilizados cinco tratamentos com quatro níveis de RBA (0, 3, 6 e 9 gramas, misturados em 220 gramas de sal proteinado) e um tratamento constituído de ectoparasiticida comercial injetável sem RBA. Não houve efeito do ectoparasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In the present study, administration of a sulphur‐containing product derived in part from garlic (Enxofre‐ Allium sativum ® ) led to a significant decrease in the number and weight of engorged female ticks, and reduced their oviposition by approximately 12%. Insect repellent, insecticidal and/or acaricidal properties have been detected in extracts of numerous plants, including garlic (Heal et al , 1950; Osmani et al , 1972; Chungsamarnyart et al , 1988; Mansingh & Williams, 1998), and a range of scientific studies have confirmed the activity of this herb (Amonkar & Banerji, 1971; Bhuyan, 1974; Jarial, 2001; Stjernberg & Berglund, 2001; Alvarenga et al , 2004). Sulphur compounds appear to be largely responsible for the acaricidal activity of garlic, although such components exhibit large variations according to both environmental and genetic factors, as well as the stage of development of the plant (Amonkar & Banerji, 1971; Tunón, 2001; Calvo‐Gomez et al , 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, administration of a sulphur‐containing product derived in part from garlic (Enxofre‐ Allium sativum ® ) led to a significant decrease in the number and weight of engorged female ticks, and reduced their oviposition by approximately 12%. Insect repellent, insecticidal and/or acaricidal properties have been detected in extracts of numerous plants, including garlic (Heal et al , 1950; Osmani et al , 1972; Chungsamarnyart et al , 1988; Mansingh & Williams, 1998), and a range of scientific studies have confirmed the activity of this herb (Amonkar & Banerji, 1971; Bhuyan, 1974; Jarial, 2001; Stjernberg & Berglund, 2001; Alvarenga et al , 2004). Sulphur compounds appear to be largely responsible for the acaricidal activity of garlic, although such components exhibit large variations according to both environmental and genetic factors, as well as the stage of development of the plant (Amonkar & Banerji, 1971; Tunón, 2001; Calvo‐Gomez et al , 2004).…”
Section: Discussionmentioning
confidence: 98%
“…An extract of Allium sativum supplied daily to animals in their concentrate supplement presented an overall efficiency of 64% compared to animals that did not receive the extract (Costa-Júnior and Furlong 2011). A similar study tested three different concentrations of residue from garlic processing and the animals with the highest ingestion of the residue had correspondingly less ticks and were not affected in weight gain (Alvarenga et al 2004).…”
Section: Natural Products For Treating Cattlementioning
confidence: 96%
“…An extract of Allium sativum supplied daily to animals in their concentrate supplement presented an overall efficiency of 64% compared to animals that did not receive the extract (Costa-Júnior and Furlong 2011). A similar study tested three different concentrations of residue from garlic processing and the animals with the highest ingestion of the residue had correspondingly less ticks and were not affected in weight gain (Alvarenga et al 2004).…”
Section: Natural Products For Treating Cattlementioning
confidence: 96%